2021
DOI: 10.1007/s11249-021-01526-7
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Simulations of Deformation Mechanism of 3C-SiC Polishing Process with a Rolling Abrasive

Abstract: In the present study, molecular dynamics (MD) simulations are applied to investigate the polishing process of cubic silicon carbide (3C-SiC) with a rotating abrasive. The influence of abrasive rotational speed and rotation axis orientation on the friction characteristics and deformation behaviors of 3C-SiC is studied. The results show that as the rotational speed increases, the normal force first increases until it reaches its maximum at 25 rad/ns and then decreases. The evolution of transverse force with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…This is due to the strong compression of the workpiece atoms in the machined region due to the high stresses generated between the tool and the workpiece during the cutting process in these three crystal orientations. This leads to a change in the initial atomic structure of the workpiece, with most of it transforming into an amorphous structure and a few atoms transforming into a hexagonal diamond structure, as also observed in the study by Yin et al 22 In addition, when machining (111) surface, vacancy atom defects were also observed below the machining area, which will adversely affect the quality and mechanical properties of the machined surface.…”
Section: Chip Morphology and Subsurface Damagementioning
confidence: 55%
“…This is due to the strong compression of the workpiece atoms in the machined region due to the high stresses generated between the tool and the workpiece during the cutting process in these three crystal orientations. This leads to a change in the initial atomic structure of the workpiece, with most of it transforming into an amorphous structure and a few atoms transforming into a hexagonal diamond structure, as also observed in the study by Yin et al 22 In addition, when machining (111) surface, vacancy atom defects were also observed below the machining area, which will adversely affect the quality and mechanical properties of the machined surface.…”
Section: Chip Morphology and Subsurface Damagementioning
confidence: 55%
“…The defects formed in this area are fully expanded and easy to form irreversible structural phase transitions, thereby affecting the number of defective atoms. In addition, the cutting movement of the tool makes the disordered movement of atoms in highly stressed workpieces more intense, increasing the number of stacked atoms, further exacerbating the evolution of atomic structural phase transitions within the workpiece [49]. Therefore, the greater the cutting depth, the more severely the intact FCC structure inside the copper-nickel alloy workpiece is destroyed, and the more atoms are formed in amorphous, HCP structure and BCC structure.…”
Section: Effect Of Nano-cutting Depths On Damage Evolutionmentioning
confidence: 99%
“…The MD simulation studies of materials are widely used to investigate the mechanical behavior and deformation mechanisms of materials at the nanoscale. It has been widely applied in the study of atomic-scale surface deformation and crystal structure and is suitable for the study of properties that are difficult to measure with many traditional experimental methods [ 27 , 28 , 29 , 30 , 31 ]. Li et al [ 32 ] employed molecular dynamics simulations to investigate the influence of cracking on GaAs deformation in different crystal orientations during processing.…”
Section: Introductionmentioning
confidence: 99%